Distribution of four Leguminosae timber species in UiTM Jengka forest reserve - Salim, Abdul Rashid; Muhamad, Khairul Adli; Tuan Asri, Tuan Mohd Shahrul Hazzem; Buhari, Zamri (2010)
The objective of this research is to study the distribution of 4 species of Leguminosae in the Forest Jengka UiTM Pahang. In addition the purposes of this study was conducted to ensure that the terrain is influencing the distribution of the growth of this species on the study of lines 1, 2, 3, 4, 5, 11, 12, 13, 14 and 15. Total specis in the study area is comprised of 35 specis Koompassia malaccensis (Kempas), Koompassia excelsa (Tualang), Instia palembanica (Merbau) and Dialium spp (Keranji). There are 11 species of Koompassia malaccensis (Kempas), 11 Dialium spp (Keranji), 7 Koompassia excelsa (Tualang) and 6 Instia palembanica (Merbau). In addition the presence of species of palm tree in the study area was made spesiss this fixation is difficult to grow up having to compete with other living species of palm tree palm species are plants that grow and grow faster than species fixation.